2020
DOI: 10.1371/journal.ppat.1008292
|View full text |Cite
|
Sign up to set email alerts
|

MyD88-dependent influx of monocytes and neutrophils impairs lymph node B cell responses to chikungunya virus infection via Irf5, Nos2 and Nox2

Abstract: Humoral immune responses initiate in the lymph node draining the site of viral infection (dLN). Some viruses subvert LN B cell activation; however, our knowledge of viral hindrance of B cell responses of important human pathogens is lacking. Here, we define mechanisms whereby chikungunya virus (CHIKV), a mosquito-transmitted RNA virus that causes outbreaks of acute and chronic arthritis in humans, hinders dLN antiviral B cell responses. Infection of WT mice with pathogenic, but not acutely cleared CHIKV, induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 66 publications
2
37
0
Order By: Relevance
“…McCarthy et al found that mice infected with a wild-type, not acutely cleared, strain of CHIKV had recruitment of monocytes and neutrophils to the draining lymph node (dLN). This aberrantly affected lymphocyte accumulation, lymph node organization, and virus-specific B cell responses, which was reversed by blocking the influx [144]. Interestingly, only pathogenic CHIKV decreased germinal center formation in the dLN, resulting in lower neutralizing antibodies in the serum compared to infection with an attenuated strain [145,146].…”
Section: Alphavirusesmentioning
confidence: 99%
See 1 more Smart Citation
“…McCarthy et al found that mice infected with a wild-type, not acutely cleared, strain of CHIKV had recruitment of monocytes and neutrophils to the draining lymph node (dLN). This aberrantly affected lymphocyte accumulation, lymph node organization, and virus-specific B cell responses, which was reversed by blocking the influx [144]. Interestingly, only pathogenic CHIKV decreased germinal center formation in the dLN, resulting in lower neutralizing antibodies in the serum compared to infection with an attenuated strain [145,146].…”
Section: Alphavirusesmentioning
confidence: 99%
“…Interestingly, only pathogenic CHIKV decreased germinal center formation in the dLN, resulting in lower neutralizing antibodies in the serum compared to infection with an attenuated strain [145,146]. These diminished B cell responses were improved upon depletion of monocytes and neutrophils during early stages of infection [144].…”
Section: Alphavirusesmentioning
confidence: 99%
“…Previous studies have revealed that the CHIKV infection induces antiviral responses by activating interferon regulatory factors (IRFs) ( 8 , 9 ). IRF-5, along with IRF-3 and IRF-7 induces the Interferon stimulated genes (ISGs) during CHIKV infection ( 10 ). Further, IRF-7–mediated type I IFN responses provide critical antiviral protection as neonatal animals lacking either of these factors succumbed to CHIKV infection ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, TLR7-dependent iNOS induction in neutrophils has not been shown before. However in murine monocytes, iNOS expression was partially TLR7-dependent after chikungunya virus infection ( McCarthy et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%